2010
DOI: 10.1111/j.1365-2125.2009.03561.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting public awareness of randomised clinical trials using the media: the ‘Get Randomised’ campaign

Abstract: AIMTo increase public awareness and understanding of clinical research in Scotland.METHODSA generic media campaign to raise public awareness of clinical research was launched in 2008. The ‘Get Randomised’ campaign was a Scotland-wide initiative led by the University of Dundee in collaboration with other Scottish universities. Television, radio and newspaper advertising showed leading clinical researchers, general practitioners and patients informing the public about the importance of randomised clinical trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 13 publications
1
39
0
2
Order By: Relevance
“…In another American study, 44 % of patients demonstrated willingness to participate or have already enrolled in clinical trials [20]. Nevertheless, a British study that surveyed 1040 subjects found that only 30.4 % of respondents expressed willingness to participate in clinical research [21]. Several studies have established that the most important barriers that discouraged patients from participating in clinical trials are fear, mistrust of the medical community, discouragement from their oncologist or family physician, financial burden, difficulties in commute, and lack of information [12].…”
Section: Discussionmentioning
confidence: 98%
“…In another American study, 44 % of patients demonstrated willingness to participate or have already enrolled in clinical trials [20]. Nevertheless, a British study that surveyed 1040 subjects found that only 30.4 % of respondents expressed willingness to participate in clinical research [21]. Several studies have established that the most important barriers that discouraged patients from participating in clinical trials are fear, mistrust of the medical community, discouragement from their oncologist or family physician, financial burden, difficulties in commute, and lack of information [12].…”
Section: Discussionmentioning
confidence: 98%
“…Other methods used to enhance trial participation, particularly in underrepresented populations, include the use of clinical registries and electronic health records [3], recruitment through community organizations, and use of media and educational outreach [21]. Few studies have evaluated the effectiveness of CT recruiting strategies [22].…”
mentioning
confidence: 99%
“…8 In another study in the United States, 44% of patients demonstrated willingness to participate or have already enrolled in clinical trials, whereas in the study in Great Britain (n = 1040), only 30.4% of the respondents conveyed their enthusiasm to participate in clinical trials. 9,10 In a previously cited Polish study, the number of people willing to participate in a clinical trial with regard to disease increases about 5-fold compared with a desire to participate as a healthy volunteer (from 15% to 71%). 6 The potential benefit of participating in a clinical trial for an oncological patient is the access to promising new treatments often not available outside the clinical trial setting -this may explain the difference.…”
Section: Discussionmentioning
confidence: 99%